2022
DOI: 10.2196/35155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Feasibility of mHealth-Supported Surgical Site Infection Diagnosis by Community Health Workers After Cesarean Section in Rural Rwanda: Randomized Controlled Trial

Abstract: Background The development of a surgical site infection (SSI) after cesarean section (c-section) is a significant cause of morbidity and mortality in low- and middle-income countries, including Rwanda. Rwanda relies on a robust community health worker (CHW)–led, home-based paradigm for delivering follow-up care for women after childbirth. However, this program does not currently include postoperative care for women after c-section, such as SSI screenings. Objective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…These studies yielded sensitivities of 70% and 72% and specificities of 100% [36,37]. While attractive for their performance qualities, and with others in SSA using such phone-based follow-up [38], we have previously found that interventions that call women for follow-up miss 38% of eligible patients in our setting [39] and that women who were less educated and with lower incomes, and therefore more vulnerable, are significantly less likely to be reached. From a health equity perspective, our team deems it unacceptable to put forward a program which further disenfranchises the most vulnerable.…”
Section: Discussionmentioning
confidence: 78%
“…These studies yielded sensitivities of 70% and 72% and specificities of 100% [36,37]. While attractive for their performance qualities, and with others in SSA using such phone-based follow-up [38], we have previously found that interventions that call women for follow-up miss 38% of eligible patients in our setting [39] and that women who were less educated and with lower incomes, and therefore more vulnerable, are significantly less likely to be reached. From a health equity perspective, our team deems it unacceptable to put forward a program which further disenfranchises the most vulnerable.…”
Section: Discussionmentioning
confidence: 78%
“…This systematic review and meta‐analysis included 17 studies with total participants of 8, 082 individuals. The study with the highest number of participants had 889 participants 13 while the study with the smallest number of participants had 93 participants. 14 The average number of participants from all 17 studies is 457 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published from 2014 to 2023. A total of 10 studies were conducted at Kirehe District Hospital, 1 , 9 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 two studies at University Teaching Hospital of Kigali, 10 , 22 and one study at University Teaching Hospital of Butare, 23 Kibungo District Hospital, 24 Ruhengeri Referral Hospital, 25 Kabgayi Hospital 14 and Bushenge Provincial Hospital each. 26 Nine studies were cohort studies, 1 , 9 , 15 , 16 , 17 , 19 , 20 , 21 , 24 six were randomized controlled trials 10 , 13 , 18 , 22 , 25 , 26 and two were cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Digital health can be another way in which CHWs can improve surgical outcomes, especially during postoperative care 33. Previous studies have provided evidence that CHWs are able to correctly diagnose surgical site infections using an app-based questionnaire and pictures of the incision site in LMICs 34 35. These interventions could help avoid poor surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%